Peran Komunikasi Edukatif Kesehatan Gigi dan Mulut Berbasis Quantum Learning pada Siswa SDN Ngringin Yogyakarta - Hidayatillah, Arifah Nurul; Vebrynda, Rhafidilla; Utami, Sri (Universitas Muhammdiyah Yogyakarta, 2026)
This study aims to analyze the role of Quantum Learning-based educational communication in shaping the dental and oral health behaviour of students of SDN Ngringin Yogyakarta. The study employs a qualitative approach with a case study design to examine the implementation of the GETHO (Good Teeth and Oral) program at Ngringin State Primary School in Sleman, Yogyakarta. Data collection was conducted through participatory observation, in-depth interviews, and documentation, then analyzed thematically and inductively. The results showed that educational communication packaged through interactive activities, multisensory learning experiences, and the application of the TANDUR scheme was able to increase student engagement and facilitate an understanding of dental and oral health messages. The GETHO program helps foster students' awareness and positive attitudes towards the importance of maintaining dental and oral health. This research confirms that the success of children's health education is not only determined by learning materials and media, but also by the design of participatory and meaningful educational communication.